Fill Two Needs With One Deed! Single-Access Protected Percutaneous Coronary Intervention With Impella Hemodynamic SupportNovel Teaching Points - Taha Ahmed, MD; Samra Haroon Lodhi, MBBS; Talha Ahmed, MD; Hafeez ul Hassan Virk, MD; Emad Dean Nukta, MD, FSCAI (CJC Open, 2020)
This report describes the case of a 64-year-old man who presented with acute coronary syndrome, depressed left ventricular function, and triple vessel disease on angiogram. The patient refused surgery and underwent high-risk percutaneous coronary intervention through the Impella sheath (Abiomed, Danvers, MA). This is one of the first known cases of single-access protected percutaneous coronary intervention, an innovative technique that brings into consideration the importance of dual vascular access via the Impella sheath. Résumé: Les auteurs décrivent le cas d’un homme âgé de 64 ans présentant un syndrome coronarien aigu, une fonction ventriculaire gauche réduite et une triple vasculopathie à l’angiogramme. Le patient a refusé une intervention chirurgicale et a plutôt subi une intervention coronarienne percutanée hautement risquée, réalisée au moyen d’une gaine Impella (Abiomed, Danvers, MA). Il s’agit de l’un des premiers cas connus d’intervention coronarienne percutanée protégée à accès unique, une technique novatrice qui met en lumière l’utilité d’un accès vasculaire double grâce à une gaine Impella.